Lack of Sequence Homology Among RNAs of Avian Leukosis-Sarcoma Viruses, Reticuloendotheliosis Viruses, and Chicken Endogenous RNA-Directed DNA Polymerase Activity - Kang, Chil-Yong (1973)
The relatedness of the RNAs of the three avian systems, including six avian leukosis-sarcoma viruses, four reticuloendotheliosis viruses, and the microsome fraction of normal uninfected chicken embryo cells, containing RNA and a DNA polymerase have been studied by nucleic acid hybridization. All six avian leukosis-sarcoma viruses have closely related nucleotide sequences; and all four reticuloendotheliosis viruses have closely related nucleotide sequences. But, almost no similarities were detected between the RNAs of avian leukosis-sarcoma viruses and reticuloendotheliosis viruses. The RNA template of the endogenous RNA-directed DNA polymerase activity of normal uninfected chicken cells had no detectable relationship to RNAs of avian leukosis-sarcoma and reticuloendotheliosis viruses.